RANCANG BANGUN MODEL PEMETAAN KECENDERUNGAN POTENSI KEWIRAUSAHAAN KE ARAH PENERAPAN TECHNOPRENEURSHIP (Studi Kasus: Program Studi Teknik Industri) - Dita Mayasai; Tiena Gustina Amran; Dedy Sugiarto (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2016)
In the Educational environment, the relationship between knowledge and technologyaffecting the organization culture. In relation to Trisakti University Vision, which is becomingthe best Industrial Engineering program and becoming the center of development for IndustrialEngineering education with technopreneurship knowledge. Big effort needs to be done to changethe student’s mindset to be entreprenurial mindset. Efforts to be done by Industrial EngineeringDepartment to achieve the vision is with the Industrial Manufacture Design Practicum, MAIRATechnopreneurship Business Incubator (MTBI) that is created to collect products by studentsand to help students doing their business, and also help them market and operate their businesswith a business incubator. The research is trying to meassure the entrepreneurial quality of eachindividual and map the student’s entrepreneurial characteristic using the IndividualEntreprenurship Quality Quesionnaire. Mapping needed to see each new students and final yearstudent’s condition. After that, what is being done is doing differentiation test to see the effect ofthe learning activities being done if it is affecting the entrepreneurial characteristic withinstudents. After the characteristics being identified, which is significant and non significant, thedevelopment of strategies will be done after that to change the non significant characteristics tobe improved. The Methodology being used in the research is T-Test and SWOT strategic Model.